Peri-urban livestock production and Development in sub-Saharan Africa: A review of the constraints and opportunities - Ehui, Simeon K.; Shapiro, Barry I.; Yapi-Gnoare, C.V. (German Foundation for International Development, 1996)
The demand for livestock products in sub-Saharan Africa is increasing steadily. This demand is driven by human population, rural-urban demographic shifts and income growth. In sub-Saharan Africa, population is expected to increase from the present 500 million to nearly 1300 million in 2025. Urbanization is also increasing rapidly. Currently, only 14.5 million people are urban dwellers, but by 2025, more than 700 million people will be living in sub-Saharan cities and towns. Between 1990 and 2025, the proportion of population living in cities, is projected to increase from 27 to 54 percent. Urbanization will force the commercialization of agriculture and increase the demand for foods of animals origin (Winrock, 1992). If livestock production does not increase, it is projected that sub-Saharan Africa will face massive deficits in meat and milk supplies by 2025. Therefore policy makers constantly face the questions of what strategies to formulate that will foster the expansion of food products to feed the growing populations. Peri-urban livestock production systems characterized by intensive commercial systems developing around cities are emerging as alternatives or mechanisms by which urban food security can be enhanced. The purpose of this paper is to review the constraints to, and opportunities for peri-urban livestock Development and discuss the role of international livestock research in contributing to sustainable food production. The paper first reviews the intensification process to highlight the stage at which peri-urban livestock systems enters the animal Development strategy. The next section gives an overview of peri-urban livestock Development systems in selected countries in SSA focusing on small ruminants and dairy. In the third section, the constraints to peri-urban livestock Development are reviewed. In the fourth section, the potential for Development of peri-urban livestock systems is addressed. The role of international lviestock research is highlighted in the fifth section.